A novel taxon of the genus Ischaemum (Poaceae: Andropogoneae: Ischaeminae) from southern Western Ghats, Kerala, India - Jabeena, Manjakulam Khadhersha; Nithya, Vadassery Madhanan; Prabhukumar, Konickal Mambetta; Athira, Subramanian; Hareesh, Vadakkoot Sankaran; Maya, Chandrasekharan Nair (Phytotaxa, 2022)
Ischaemum sunilii, a new grass species from Nelliyampathy hills of southern Western Ghats, Kerala, India, is described and illustrated. The new species is allied to I. rangacharianum, but differs in many attributes. Description of the new species with distribution, ecology and comparison with its allied taxa are provided.